Students’ Perception of Using Canva Aplication in Writing Short Functional Text - Denti Zentia Putri; Syafryadin Syafryadin (Universitas Galuh, 2023)
The aims of this study were to investigate the students' perception of ‘Canva for Education’ in writing short functional text (greetings card) at MTSN 2 Kepahiang, in the academic year 2021/2022. The research used descriptive qualitative with a questionnaire using Likert scale. The questionnaire was conducted by students of class VIII as the chosen sample of this study by using purposive sampling. The data instrument of this study was a questionnaire. The research showed on the students’ perception toward the use of ‘Canva for Education’ in writing short functional text (greetings cards) gave several benefits to their experience and for enhance students’ ability and they felt enthusiastic about learning by using ‘Canva for Education’. Using Canva has a good effect on students. combined with greeting cards lessons also make them able to develop creativity and make teachers able to innovate and of course provide benefits in the process of improving student writing.